Arbitrage opportunities with a delta-gamma neutral strategy in the Brazilian options market - Processi, Lucas Duarte (2017)
We investigate arbitrage opportunities in the Brazilian options market. Our research consists inbacktesting several delta-gamma neutral portfolios of options traded in B3 exchange to assessthe possibility of obtaining systematic excess returns. Returns sum up to 400% of the dailyinterbank rate in Brazil (CDI), a rate viewed as risk-free. However, with bootstrap analysis,we find evidence consistent with the absence of arbitrage opportunities in the Brazilian optionsmarket.This approach is different from other studies because the analysis is taken on several options ondifferent underlying assets, which gives us the opportunity to investigate factors that influencethe magnitude of excess returns. Europeanness is the most relevant factor found.